Updated peer review of the pesticide risk assessment of the active substance mepanipyrim - Álvarez, Fernando; Arena, Maria; Auteri, Domenica; Batista Leite, Sofia; Binaglia, Marco; Castoldi, Anna Federica; Chiusolo, Arianna; Cioca, Ana‐Andreea; Colagiorgi, Angelo; Colas, Mathilde; Crivellente, Federica; De Lentdecker, Chloe; et al. (EFSA journal, 2023)
The conclusions of the EFSA following the peer review of the initial risk assessments carried out by the competent authorities of the rapporteur Member State, Belgium, and co‐rapporteur Member State, Greece, for the pesticide active substance mepanipyrim are reported. The context of the peer review was that required by Commission Implementing Regulation (EU) No 844/2012. The conclusions were reached on the basis of the evaluation of the representative uses of mepanipyrim as a fungicide on table and wine grapes and in field and protected strawberries and tomatoes. The conclusions were updated with regard to the endocrine‐disrupting properties following a mandate received from the European Commission in January 2019. The reliable end points appropriate for use in regulatory risk assessment are presented. Missing information identified as being required by the regulatory framework is listed. Concerns are reported where identified.